ANALISIS EFISIENSI PENGGUNAAN FAKTOR –FAKTOR PRODUKSI PADA USAHA KECIL DAN MENENGAH BATIK DI KELURAHAN KAUMAN KOTA PEKALONGAN - akhmad hidayat (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
The research want to know about influence of asset, labor, and main material toward production values , and analyzes of technical efficiency, cost efficiency, and economic efficiency in small and medium business in Kauman, Pekalongan uses primary data from 33 unit batik entrepreneur in Kauman, Pekalongan. Data were analyzed by quantitative-description method, regression, and efficiency analysis. Result of research shows that main material and asset influence to production price of little and middle batik business in Kauman, Pekalongan, but labor variable doesn’t influences. T-test shows that asset variable and main material variable give positive influence toward production price of batik. Efficiency count shows that techniques efficiency is 0,8427. Efficiency price is 2,3221; economic efficiency is 1,9568; and return to scale value is 4,525. That is shows the position of batik business at increasing return to scale